Transcriptome and Genome Analyses Applied to Aquaculture Research - Pereiro, Patricia (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Aquaculture is an important economic activity for food production all around the world that has experienced an exponential growth during the last few decades. However, several weaknesses and bottlenecks still need to be addressed in order to improve the aquaculture productive system. The recent fast development of the omics technologies has provided scientists with meaningful tools to elucidate the molecular basis of their research interests. This reprint compiles different works about the use of transcriptomics and genomics technologies in different aspects of the aquaculture research, such as immunity, stress response, development, sexual dimorphism, among others, in a variety of fish and shellfish, and even in turtles. Different transcriptome (mRNAs and non-coding RNAs (ncRNAs)), genome (Single Nucleotide Polymorphisms (SNPs)), and metatranscriptome analyses were conducted to unravel those different aspects of interest.